The incidence of malaria in travellers to South-East Asia: is local malaria transmission a useful risk indicator? - Behrens, Ron H.; Carroll, Bernadette; Hellgren, Urban; Visser, Leo G.; Siikamäki, Heli; Vestergaard, Lasse S.; Calleri, Guido; Jänisch, Thomas; Myrvang, Bjørn; Gascon, Joaquim; Hatz, Christoph (Malaria journal, 2010)
The presence of ongoing local malaria transmission, identified though local surveillance and reported to regional WHO offices, by S-E Asian countries, forms the basis of national and international chemoprophylaxis recommendations in western countries. The study was designed to examine whether the strategy of using malaria transmission in a local population was an accurate estimate of the malaria threat faced by travellers and a correlate of malaria in returning travellers.
Gesehen am 05.01.2023